Intracardiac rhabdomyoma in a newborn with tuberous sclerosis - I Kadek Suarca; Ida Bagus Agung Winaya; I Komang Kari (Paediatrica Indonesiana, 2006)
Primary congenital cardiac tumors, especiallyintracardiac tumors, are rare in children.Rhabdomyoma is the most common oneand usually diagnosed in the first few days oflife. Referral from pediatric cardiac centers found thatthe incidence of cardiac tumors was 0.08%-0.20%.Rhabdomyoma represents 36%-42% in autopsy seriesand 79% in clinical series.